Theoretical investigation of bulk acoustic waves with high electromechanical coupling coefficient in c-axis-tilted wurtzite ScAlN - Takumi Tominaga (AIP Advances)
Scandium aluminum nitride (ScAlN) has gained significant attention as a piezoelectric material for bulk acoustic wave (BAW) resonators, offering a promising alternative to conventional aluminum nitride (AlN) due to its superior piezoelectric properties. Recent advancements in ScAlN film fabrication techniques, enabling control over the Sc concentration (x) and c-axis tilt angle (θ), have motivated this study to theoretically investigate the BAW propagation characteristics of c-axis-tilted ScxAl1−xN as a function of x and θ. In c-axis-tilted ScAlN, quasi-longitudinal and quasi-shear waves coupled with piezoelectricity propagate, with their electromechanical coupling coefficient (K2) values increasing sharply with x and reaching maximum values under different conditions: θ = 0° for quasi-longitudinal waves and θ = 32.35° for quasi-shear waves. At x = 0.43, where ScAlN exhibits its highest piezoelectricity, the maximum K2 values are 24.7% and 32.1% for quasi-longitudinal and quasi-shear waves, respectively, 4.3 and 5.3 times higher than those of AlN. This increase in K2 is attributed to a reduction in elastic constants and enhanced piezoelectric stiffening of ScAlN with increasing x, accompanied by a decrease in phase velocity. The substantial enhancement in K2 values for quasi-longitudinal and quasi-shear waves with increasing x underscores the primary advantage of c-axis-tilted ScAlN. This improvement enables c-axis-tilted ScAlN to overcome the limitations of AlN in BAW propagation characteristics, offering the potential for advanced performance in BAW resonators.